Byzantium as Christian Antiquity - Zakharova, Anna V.; Mal’tseva, Svetlana V. (Actual Problems of Theory and History of Art, 2015)
The article is focused on the problem of the relations between art of Classical antiquity and that of Byzantium. On the one hand, it is evident that the latter is the successor to the former. On the other hand, it is clear that the latter is quite different, sometimes opposite to the former. Throughout the 20th century scholars dealt with this issue differently. The authors of this article align with the approach that considers the Byzantine millennium as the continuation of Classical tradition spiritually enriched by Christianity. This study shows how some Classical architectural and iconographic models were preserved and gradually transformed into a new artistic system that was able to adequately embody new religious contents.